Association between dietary vitamin C intake and risk of esophageal cancer: A dose–response meta‐analysis. Issue 8 (15th October 2015) - Bo, Yacong; Lu, Yan; Zhao, Yan; Zhao, Erjiang; Yuan, Ling; Lu, Weiquan; Cui, Lingling; Lu, Quanjun
Abstract : While several epidemiological studies have investigated the association between vitamin C and risk of esophageal cancer, the results remain inconsistent. In the present study, a meta‐analysis was conducted to assess the impact of dietary vitamin C intake on esophageal cancer risk. Online databases were searched up to March 29, 2015, for studies on the association between dietary vitamin C intake and esophageal cancer risk. Pooled risk ratios (RRs) or odds ratios (ORs) and 95% confidence intervals (CIs) were calculated using a random‐effects model. Dose–response analyses were performed using the method of restricted cubic splines with four knots at percentiles of 5, 35, 65 and 95% of the distribution. Publication bias was estimated using Egger's tests and funnel plots. In all, 15 articles were included in this meta‐analysis, including 20 studies, containing 7063 controls and 3955 cases of esophageal cancer. By comparing the highest vs . the lowest categories of vitamin C intake, we found that vitamin C was inversely associated with the risk of esophageal cancer [overall OR = 0.58, 95% CI = 0.49–0.68, I 2  = 56%]. A linear dose–response relationship was found. With an increase in dietary vitamin C intake of 50 mg/day, the risk of esophageal cancer statistically decreased by 13% (OR = 0.87, 95% CI = 0.80–0.93, p linearity  = 0.0002). In conclusion, our analysis suggested that the higher intake of dietary vitamin C might have a protective effect against esophageal cancer.